Solving Software Challenges for Exascale : International Conference on Exascale Applications and Software, EASC 2014, Stockholm, Sweden, April 2-3, 2014, Revised Selected Papers - Markidis, Stefano; Laure, Erwin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume contains the thoroughly refereed post-conference proceedings of the Second International Conference on Exascale Applications and Software, EASC 2014, held in Stockholm, Sweden, in April 2014. The 6 full papers presented together with 6 short papers were carefully reviewed and selected from 17 submissions. They are organized in two topical sections named: toward exascale scientific applications and development environment for exascale applications.
Tackling Exascale Software Challenges in Molecular Dynamics Simulations with GROMACS.- Weighted Decomposition in High-Performance Lattice-Boltzmann Simulations: Are Some Lattice Sites More Equal than Others.- Performance Analysis of a Reduced Data Movement Algorithm for Neutron Cross Section Data in Monte Carlo Simulations.- Nek5000 with OpenACC -- Auto-tuning an OpenACC Accelerated Version of Nek5000 -- Development Environment for Exascale Applications Towards Exascale Co-Design in a Runtime System.- Overcoming Asynchrony: An Analysis of the Effects of Asynchronous Noise on Nearest Neighbor Synchronizations.- Memory Usage Optimizations for Online Event Analysis.- Towards Detailed Exascale Application Analysis Selective Monitoring and Visualisation.- Performance Analysis of Irregular Collective Communication with the Crystal Router Algorithm.- The Architecture of Vistle, a Scalable Distributed Visualization System. .
Keywords: Computer software; Software engineering; Computer Communication Networks; Artificial intelligence; Computer simulation; Computer science; Algorithm Analysis and Problem Complexity; Software Engineering; Computer Communication Networks; Artificial Intelligence; Simulation and Modeling; Programming Techniques